Peningkatan Pengetahuan dan Keterampilan Kader Posyandu dalam Mencegah Stunting - Grouse Oematan; Gustaf Oematan; Utma Aspatria (Yayasan Sumber Daya Manusia Cerdas, 2023)
Posyandu cadres have a role in delivering basic health services to pregnant women, infants, toddlers, children and families. Cadres are an integral part of posyandu management in the community. Good knowledge and skills are needed to support the duties of a cadre. This service activity aims to increase the knowledge and skills of posyandu cadres in Tanah Putih Village. There were 12 participants in this activity. Increasing the knowledge and skills of cadres is carried out through counseling and simulations. Based on the results of evaluating the level of knowledge regarding stunting, the first 1000 days of life (HPK), monitoring of child growth and development as well as the skills of cadres regarding filling out the health card (KMS) experienced a significant increase.